Up from nothing : the Michigan State University Cyclotron Laboratory - Austin, Sam M. (Michigan State University, 2015)
Up from Nothing is the story of the Michigan State University Cyclotron Laboratory and its growth from the appointment of a single individual in 1958 to when the university earned the right to build the Facility for Rare Isotope Beams (FRIB) in 2008. The cyclotron laboratory at MSU has been known for years as the best university nuclear physics laboratory in the United States, and perhaps in the world. But very few, even in its hometown of East Lansing, know how it achieved that status or why it prospered when laboratories at many other famous universities faded. In this book Austin, a nuclear physicist who has been at the laboratory since the beginning of its ascent, gives us a remarkable story. It begins with an exceptional individual, Henry Blosser, who founded the laboratory, built a cyclotron accelerator of uniquely high precision, and recruited a team of nuclear physicists that used it to establish the laboratory's reputation. Its credibility led to a sequence of accelerators, each operating in a different sub?eld while continuing a tradition of forefront science, and to a laboratory culture that fostered the courage and foresight to compete for the FRIB in the face of daunting odds.